Agro-Based Catalyst Systems For Converting Palm Based Oils With High Fatty Acids And Water Contents Into Methyl Esters - Ganesan, Shangeetha (2012)
Present work focuses on producing a dual catalyst system to esterify fatty acids and . transesterify triglycerides into methyl esters in the presence of methanol. Firstly, boiler ash sourced from waste empty fruit bunches of the palm oil industry was characterized and used as a pseudo-homogeneous base catalyst for transesterification of palm olein. Boiler ash successfully transesterified palm olein at mild reaction conditions (3 wt.% dried boiler ash, 15: 1 methanol : oil molar ratio, methanol refluxing temperature and reaction time of 0.5 b) to produce 90% methyl esters. Calcium oxide (calcined at 900 oe for 2 h) was added to boiler ash in order to increase the free fatty acids and water tolerance of boiler ash for transesterification of low quality oils. A mixture of boiler ash-calcium oxide was found to be able to tolerate 3 wt.% water and 4 wt.% free fatty acids.